Agronomic yield and economic performance of maize in different management levels and sowing times - Forsthofer, Everton Leonardo; Silva, Paulo Regis Ferreira da; Strieder, Mércio Luiz; Minetto, Tarcísio; Rambo, Lisandro; Argenta, Gilber; Sangoi, Luis; Suhre, Elias; Silva, Adriano Alves da (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate agronomic and economic performance of maize in five management levels and three sowing times. The experiment was conducted in 2001/2002 and 2002/2003, in Eldorado do Sul, RS, Brazil. Treatments consisted of three sowing times (August, October and December) and five management levels (low, average, high, potential I and II) which varied in relation to the soil winter cover, cultivar, plant arrangement and the level of chemical fertilizer, water supply and weed, insect and disease control. A randomized block design was used with split-plots and four replications. Sowing times were located in the main plots and the management level in the split-plots. The increments in maize yield in response to investments in management and cultivar were higher in August and October, and resulted in higher economic return, mainly in October. In December sowing, there was no economic return for the highest investment in management level. In August and October, it was possible to associate maximal economic and technical efficiencies through the management level increase and the choice of the greater potential yield cultivar.